Evaluasi Program Pelestarian Budaya Lampung : Bahasa dan Aksara (Studi Penilaian Aplikasi Kaganga Di Kota Bandar Lampung) - Heri Indrawansyah; Susana Indriyati Caturiani; Vina Karmilasari (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
Lampung Province's Culture of Language and Script that is rarely used both in pronunciation and in learning for students. With that the education and culture office of Lampung Province invites cooperation with the Lampung Language MGMP to create a program about Lampung culture by creating a mobile application that contains content about the Lampung Language and Script. The purpose of this study was to find out an explanation of the Lampung Language and Script Preservation Program through the Kaganga Application in Bandar Lampung City. This research uses descriptive qualitative research with data collection techniques including interviews, observation and documentation. The results of this study indicate that the implementation of the Lampung culture preservation program, namely Language and Script in the Kaganga application issued by the education and culture office of Lampung Province, has been running quite well, but there are still several evaluation criteria that have not been implemented optimally in the application of the program issued by the department of education. Lampung Province Education and Culture